Conversations between economists and anthropologists - "Bardhan, Pranab (ed.)" (Delhi, 1989)
A wide methodological gulf separates economists and anthropologists. As the author says, the image of economists is that of "mimic physicists crackling with the static of electronic data", while anthropologists "smell of outdoors and manure". Some of the basic purposes of this book are to bridge this methodological gap, to blur the conventional images of the economist and the anthropologist and to nudge scholars within both these disciplines towards meaningful conversation and common ground. These purpose are achieved in part by focusing upon one of the most basic areas explored by both economists and anthropologists who work in India and the developing world - measuring economic change in rural areas.
Keywords: Economic history - India